Peranan Dakwah dalam Pengumpulan Zakat Maal di Baznas Kabupaten Takalar - Syarifah Johar (MERCUSUAR : Jurnal Komunikasi dan Penyiaran Islam, 2022)
This research aims to examine the process of preaching in the collection of maal zakat in Takalar Regency and to analyze the forms of preaching in the collection of maal zakat in Takalar Regency. This research uses a descriptive qualitative research design located at Baznas Takalar Regency. The approach used by the researcher is the dakwah science approach. The primary data sources for this research are the informants, with the key informant being the Chairman of Baznas Takalar Regency, and additional informants being members of Baznas. Secondary data sources include books, the internet, ebooks, journals, and other data sources that complement the study. The data collection methods used are observation, interviews, and documentation. Data analysis is conducted through three stages: data reduction, data presentation, and drawing conclusions. The results of this research indicate that the preaching process in the collection of maal zakat in Takalar Regency includes: 1) Formation of zakat task force, where the zakat task force is formed by Baznas by appointing Islamic Religious Counselors in Takalar Regency. 2) Improving cooperation, where Baznas has collaborated with the Ministry of Religious Affairs in Takalar Regency by appointing Counselors as zakat task force with the hope of maximizing maal zakat collection activities in Takalar Regency. As a form of preaching in the collection of maal zakat in Takalar Regency, there are several forms of preaching used, namely: 1) Dakwah bil hal, which is preaching that applies tangible actions or deeds. 2) Dakwah bil lisan, which is preaching that conveys messages orally, in the form of speeches used in the community during certain events. 3) Dakwah bil qalam, which is preaching that conveys messages through writing, such as creating pamphlets.